2020
DOI: 10.1111/ijlh.13238
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review about etiologic association to the leukoerythroblastic reaction

Abstract: Background and purpose Leukoerythroblastic reaction (LER) is characterized by the presence of immature erythroid cells and myeloid precursors (metamyelocytes, myelocytes, promyelocytes, myeloblasts, and blasts) as well as, exclusively in myelofibrotic disorders, teardrop cells in the peripheral blood (J Pathol Bacteriol, 42, 1936, 541; Semaine Med, 22, 1902, 373). Research on how to interpret LER and its meaning in clinical practice is scarce, and there is no consensus on the diagnostic criteria. We summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…The presence of NRBC in peripheral blood is an important finding, indicating not only pathologic conditions but also patient prognostication 3‐11 . The manual count has been the standard method for detection and enumeration of circulating NRBCs, adopted by most hematology laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of NRBC in peripheral blood is an important finding, indicating not only pathologic conditions but also patient prognostication 3‐11 . The manual count has been the standard method for detection and enumeration of circulating NRBCs, adopted by most hematology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the presence of such cells in peripheral blood of older children and adults signifies a pathological state of the bone marrow. Possible causes include hematopoietic stress, bone marrow damage, massive hemorrhage, and severe hypoxia, which usually lead to hematology consultation and, in some cases, invasive investigation like bone marrow examination 3‐7 …”
Section: Introductionmentioning
confidence: 99%
“…It is defined as a condition in which there is a presence of immature myeloid cells and nucleated red blood cells in the circulating blood [4]. LER is most commonly seen in patients with metastatic malignancies, but Clifford was the first to describe it in conditions other than cancer, including hemolytic anemia, blood loss (acute or chronic), congestive heart failure, sepsis, megaloblastic anemia, and tuberculosis [5][6][7]. LER is usually not seen in viral infections, except for one study by Lemont et al in 2011 that showed LER can rarely be seen in parvovirus B19 infection [8].…”
Section: Discussionmentioning
confidence: 99%
“…El síndrome leucoeritroblástico puede aparecer en diferentes enfermedades neoplásicas (1,2) , infecciosas (Parvovirus B19 (3) , malaria grave (4) ), mielofibrosis, anemias hemolíticas o hemorragia grave. Es muy poco frecuente en la población pediátrica, limitado de forma casi exclusiva a procesos infecciosos (5) .…”
Section: Leukoerythroblastic Reaction Unusual Presentation Of Acute Leukemia In Childrenunclassified